Peran Baznas Sebagai Filantropi Islam Dalam Menopang Ekonomi Masyarakat Ditengah Pandemi Covid-19 - Nada Shofiya Nabila; Dini Diah Fistasari; Habibah Awwaliah; Noor Wahyudi (Ekonomi Islam, 2021)
The serious impact of Covid-19 also occurred in the economic sector, while economic activities did not run as it should so that the community could not work and could not meet their daily needs. This should not be directly about the amount of poverty in Indonesia. Zakat as an Islamic financial instrument is not only intended to fulfill the necessities of mustahik life, but can be used as an instrument in economic development. The purpose of this choice is to discuss the role of zakat institutions in economic problems caused by the Covid-19 pandemic. This study uses qualitative methods with a research format or descriptive research. The results of the study stated that the Zakat Institution (BAZNAS) proposes to be a media and a means of distributing assistance to the Covid-19 affected communities through socio-economic emergency programs whose distribution is right on target. BAZNAS has focused the distribution of zakat funds into two programs that are urgently needed by the community, namely the emergency health program and the emergency socioeconomic program.Keywords: Philanthropy, BAZNAS, Economics, Covid-19, Zakat